Work-life balance among teaching hospital nurses in Malaysia - Nurumal, Mohd. Said; Makabe, Sachiko; Che Jamaludin, Farah Ilyani; Mohd Yusof, Hairil Fahmi; Aung, Khin Thandar; Kowitlawakul, Yanika (Canadian Center of Science and Education, 2017)
Extreme workload and poor working environment have a negative impact on the emotional and physical statuses among nurses. The study has contributed to evaluate work-life balance and its related factors among teaching hospital nurses. It was aimed to examine the work-life balance and its related factors among teaching hospital nurses. A cross-sectional study using a universal sampling technique was conducted. 1002 nurses were included from the Teaching hospital of Klang Valley, Malaysia. The instrument was adapted from NIOSH Generic Job Stress Questionnaire and QoL questionnaire from WHO, and it was used to measure the quality of work-life balance. Non-work activities, job requirement, supervisor support, job satisfaction, manageability, social and environmental variables have independently influenced work-life balance among nurses. Furthermore, quality of life variables has positively influenced the work-life balance (P<0.050). Work life balance and organizational commitment can have a positive relationship. Whereas, Nurses working in fixed shifts were observed with greater work-life balance as compared to the nurses working in multiple shifts. A friendly environment in the professional sector plays a major role for developing motivation and enthusiasm among workers.